2021
DOI: 10.3390/ijms23010078
|View full text |Cite
|
Sign up to set email alerts
|

Possible Role of Circulating Bone Marrow Mesenchymal Progenitors in Modulating Inflammation and Promoting Wound Repair

Abstract: Circulating bone marrow mesenchymal progenitors (BMMPs) are known to be potent antigen-presenting cells that migrate to damaged tissue to secrete cytokines and growth factors. An altered or dysregulated inflammatory cascade leads to a poor healing outcome. A skin model developed in our previous study was used to observe the immuno-modulatory properties of circulating BMMP cells in inflammatory chronic wounds in a scenario of low skin perfusion. BMMPs were analysed exclusively and in conjunction with recombinan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…In current study, biochemical analysis of granulation tissue revealed significantly elevated levels of hexuronic acid, hydroxyproline and hexosamine in EGTE group compared to levels in vehicle control and distilled water group. Measurement of hydroxyproline and hexosamine has been used as index of collagen turnover and collagen is a predominant protein of the extracellular matrix [ 48 ]. In addition to this increased amount of hexosamine content in rabbits treated with EGTE is an indication of collagen fiber stabilization mediated by means of electrostatic and ionic interactions [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In current study, biochemical analysis of granulation tissue revealed significantly elevated levels of hexuronic acid, hydroxyproline and hexosamine in EGTE group compared to levels in vehicle control and distilled water group. Measurement of hydroxyproline and hexosamine has been used as index of collagen turnover and collagen is a predominant protein of the extracellular matrix [ 48 ]. In addition to this increased amount of hexosamine content in rabbits treated with EGTE is an indication of collagen fiber stabilization mediated by means of electrostatic and ionic interactions [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, the terms medicinal signaling cells and mesenchymal progenitors have started to be used by experts in the field to replace previous names to refer to MSCs [ 2 , 3 , 4 ]. Nevertheless, we are going to use the latter to avoid confusion.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…The previous regulatory agencies were mentioned because they have until now been the only ones that could approve CTMP therapies that use their originally baptized mesenchymal stem cell name (commonly referred to as MSCs); these agencies have attempted to change their name to medicinal signaling cells, and more recently to mesenchymal progenitors (Arnold I. Caplan, personal communication; see Acknowledgement statement). For convenience, the term MSCs will be used from here on [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, the terms medicinal signaling cells and mesenchymal progenitors have begun to be used by experts in the field with the intention of replacing previous names used to refer to MSCs [2][3][4]. Nevertheless, we are going to use the latter to avoid confusion.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…The CTMP therapies use mostly what originally were baptized as mesenchymal stem cells (commonly referred to as MSCs) and later attempted to be changed for medicinal signaling cells, and more recently for mesenchymal progenitors (Arnold I. Caplan, personal communication 2022). For convenience, the term MSCs will be used here [2][3][4].…”
Section: Introductionmentioning
confidence: 99%